THE USAGE OF JARIMATIKA METHODS TO IMPROVE COUNTING SKILLS ABILITY FOR LOW-GRADE STUDENTS - Ihsanudin, Ihsanudin; Alamsyah, Trian Pamungkas (Universitas Muria Kudus, 2019)
The purpose of this research is to find the usage of Jarimatika method in improving counting skills ability for low grade students on multiplication 6 to 10. The method used in this study is a quasi-experimental method. The sample of this study is grade III elementary school. Sample selection by purposive sampling. The study was conducted at SD Banjar Agung 4 Serang Regency with a population of all class III at the elementary school. Data was collected using several techniques of documentation, observation, tests and interviews. This study uses a prerequisite test that is normality test and homogeneity test using SPSS 19 program.The results of this study, there is an improvement in students? counting skills on multiplication 6 to 10 which can be seen by increasing the average score of students in the post test and based on the calculation of the t test with a significant value of 0.343 (exceeded the value of 0.05) and students are more enthusiastic and not quickly forget the multiplication calculation.